2014
DOI: 10.1155/2014/727049
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Biodegradation of Palm Oil Mill Effluents by Local Isolated Microorganisms

Abstract: This study was designed to investigate the microorganisms associated with palm oil mill effluent (POME) in Johor Bahru state, Malaysia. Biodegradation of palm oil mill effluents (POME) was conducted to measure the discarded POME based on physicochemical quality. The bacteria that were isolated are Micrococcus species, Bacillus species, Pseudomonas species, and Staphylococcus aureus, while the fungi that were isolated are Aspergillus niger, Aspergillus fumigatus, Candida species, Fusarium species, Mucor species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
26
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 25 publications
6
26
0
2
Order By: Relevance
“…Chin et al (1996) have reported that POME contains a high concentration of organic matter, COD concentration in the range of 45,000-65,000 mg/L and BOD of 18,000-48,000 mg/L. COD in the range of 80,100-95,000 mg/L and BOD of 23,400-52,100 mg/L has also been encountered (Soleimaninanadegani and Manshad 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Chin et al (1996) have reported that POME contains a high concentration of organic matter, COD concentration in the range of 45,000-65,000 mg/L and BOD of 18,000-48,000 mg/L. COD in the range of 80,100-95,000 mg/L and BOD of 23,400-52,100 mg/L has also been encountered (Soleimaninanadegani and Manshad 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A high concentration of organic matter, COD (45,000 to 65,000 mg/L) and BOD (18,000 to 48,000 mg/L) of POME was reported by Chin et al (1996). Soleimaninanadegani and Manshad (2014) reported a COD and BOD in the range of 80,100 to 95,000 and 23,400 to 52,100 mg/L, respectively. A COD and BOD of 40,000 to 50, 000 and 20,000 to 25,000 mg/L were reported by Najafpour et al (2006).…”
Section: Introductionmentioning
confidence: 88%
“…have been well studied for their ability to produce lipolytic enzymes (Burkert et al, 2004;D'Annibale et al, 2006;Grbavcic et al, 2007;Nwauche and Ogbonna, 2011). Though, POME is a major environmental concern, only limited studies were reported its bioremediation (Oswal et al, 2002;Wu et al, 2010;Soleimaninanadegani and Manshad, 2014). Therefore, screening and isolation of fungi from POME dump sites provides an alternative way to clean up environmental pollutants as these microbes use the organic compounds present in the POME as supplements and thereby degrade these substances into simpler compounds like methane, carbon dioxide and water.…”
Section: Introductionmentioning
confidence: 99%
“…One way to acquire the potential bacteria in degraded liquid waste while using POME as a nutritional source is to isolate with specific media in its ability to test. Pseudomonas species, Staphylococcus aureus, and Bacillus species are some examples of bacteria that produce lipase [19]. The purple phototrophic bacteria can be used for the upgrading of biogas from the treatment of piggery wastewater.…”
Section: Introductionmentioning
confidence: 99%